The ruminant livestock industry EFFECT OF TYPE AND DOSAGE OF FOLIAR FERTILIZERS ON DIGESTIBILITY AND NUTRIENT CONTENT OF BUTTERFLY PEA (Clitoria ternatea): PENGARUH JENIS DAN DOSIS PUPUK DAUN TERHADAP KECERNAAN DAN KANDUNGAN NUTRIEN KEMBANG TELANG (Clitoria ternatea) - Sariffudin, Apriyani Nur; Umami, Nafiatul; Suhartanto, Bambang; Ahmad, SN (Universitas Djuanda, 2024)
The study aimed to determine the effect of the type and dose level of foliar fertilizers on the nutrient content and in vitro digestibility of Clitoria ternatea. The research was conducted at Faculty of Animal Science, Gadjah Mada University. The materials used were butterfly pea seeds, rabbit liquid organic and Gandasil®D fertilizer, rumen fluid. The study analysed by Completely Randomized Design (CRD) with factorial 2x4. The first factor was the type of foliar fertilizer (rabbit liquid organic and Gandasil®D fertilizer). The second factor was the level of fertilizer dosage (0, 1.5, 3 and 4.5 g/l/plot). Parameters observed were DM, OM, Ash, CP, CF, Crude Fat, in vitro dry matter and organic matter digestibility (IVDMD/IVOMD). Data were analyzed by variance analysis at 5%, continued with Duncan's Multiple Range Test (DMRT). The results showed that the types of foliar fertilizers didn’t significantly affect the nutrient content (P>0.05), but had a significant effect on IVDMD and IVOMD (P<0.05). The dose level had a significant effect on CP, CF, IVDMD, IVOMD (P<0,05), but not significant effect on DM, OM, and crude fat (P>0.05). There was an interaction between type and dose level of foliar fertilizer on IVDMD and IVOMD (P<0.05). The conclusion is the type of foliar fertilizer doesn’t affect the nutrient content while the level of fertilizer dosage has a significant effect. There is a combination of foliar fertilizers and dose levels on IVDMD and IVOMD. The combination of Gandasil®D fertilizer with dose level of 4,5 g/l/plot got the best IVDMD and IVOMD.